Biomarkers of residual risk and all-cause mortality after acute coronary syndrome. - Anna Toso; Mario Leoncini; Mauro Maioli; Simona Villani; Francesco Bellandi (American Journal of Preventive Cardiology)
Background: Adverse cardiovascular events often recur after acute coronary syndrome (ACS), despite secondary prevention measures. Residual risk involves various inflammatory, metabolic and renal factors as well as lipid and thrombotic processes. This cohort study investigates the relationship between four risk biomarkers at 1 month after ACS and all-cause death within 3 years in patients treated with early invasive strategy and high-intensity statins from admission. Methods: Levels of residual risk for the biomarkers were: low-density lipoprotein cholesterol (LDL-C) ≥ 70 mg/dl; high-sensitivity C reactive protein (hs-CRP) ≥ 2 mg/l; glycosylated hemoglobin (HbA1c) ≥ 7% in diabetic and ≥ 5.7% in non-diabetic patients; decrease in estimated glomerular filtration rate (eGFR) ≥ 25% compared to baseline. The association between the four biomarkers and all-cause death within 3 years was evaluated with Cox proportional analysis. Results: This study included 1099 patients (68±12 years; 70.3% males). At 1 month the majority of patients had levels of LDL-C, hs-CRP and/or HbA1c above the risk cut-points, and only 7% of cases presented reduced eGFR. Reduced eGFR and hs-CRP ≥ 2 mg/l at 1 month were the sole independent biomarker predictors of 3-year mortality (adjusted hazard ratios 3.03 and 2.66, respectively). Conclusions: In this population on high-intensity statin therapy only hsCRP and eGFR were independently associated with medium-term mortality. Diversification of secondary preventive measures based on routine evaluations of inflammation and kidney function markers, not only LDL-C, could lead to better targeted reduction of residual risk after ACS.